PENDUGAAN POTENSI VOLUME DAN BIOMASSA TEGAKAN JABON MERAH ( Anthocepalus macropillus) PADA HUTAN PRODUKSI TERBATAS (HPT) - Saputra, Tandi Medita; h, Hamzari; Muis, Hasriani (Jurnal Warta Rimba, 2019)
Red Jabon naturally, grows in the lowland Sulawesi forest to the mountains. One of the locations where the Jabon Merah distribution is found is in the KPH Sivia Patuju management area. Plot determination in this study used a systematic sampling with random star method, with a plot size of 20 m X 125 m as many as 30 plots and a distance between plots of 50 meters. The results of the field data will be entered into a tally sheet, then to calculate the potential, a formula is used to interpret Jabon's potential and allometrics to calculate its biomass by statistical analysis. Based on the results of direct research in the field and analysis of data that has been carried out, the data obtained are the estimation of the potential volume of the Red Jabon tree (Anthocepalus macropillus) which is in the Limited Production Forest (HPT) of Tatari Village, West Tojo District, Tojo Una-una District, which is 198,873, 2 mÂ³ and volume 267.64 mÂ³/ha. And estimation of Biomass found in Jabon Merah stands (Anthocepalus macropillus) overall biomass of 112,870.2 tons and Biomass on average 151.5 tons/ha.